Penyelesaian Sengketa Bisnis Keuangan Islam Melalui Pengadilan di Malaysia dan Relevansinya dengan Indonesia - Agus Triyanta; Rusni Hassan (Jurnal Hukum IUS QUIA IUSTUM, 2008)
Islamic financial transactions, particularly in Islamic banking business, is a new mode of financial transaction in the nomenclature of the law of contracts. Different from conventional financial transactions which have been established for a long time, Islamic financial transaction is a newly introduced and is still evolving to find out its ideal form. Having said this, dispute settlement for cases arising from the Islamic financial transactions certainly need sufficient attention from the judicial authority in Indonesia. If for about fiveteen years dispute settlement in this matter was under the authority of the Shariah Arbitration Panel (Basyarnas), today, this dispute settlement can be brought to the court of juctice. It is made possible by virtue of the issuance of the Act no. 3 of 2006 on Religious Court and also the approval of the bill of Shariah Banking Act by the members of parliament. This fact suggests that for Indonesia necessary preparations pertinent to the court sistems to be rady in hadling the cases are strongly demanded. In this situation, Malaysia’s experiences in matters pertinent to dispute settlement of Islamic financial business through the court is a good case to be learned.